Results from Genetic Studies in Patients Affected with Craniosynostosis: Clinical and Molecular Aspects - Bukowska-Olech, Ewelina; Sowińska-Seidler, Anna; Larysz, Dawid; Gawliński, Paweł; Koczyk, Grzegorz; Popiel, Delfina; Gurba-Bryśkiewicz, Lidia; Materna-Kiryluk, Anna; Adamek, Zuzanna; Szczepankiewicz, Aleksandra; Dominiak, Paweł; Glista, Filip; et al. (Frontiers in Molecular Biosciences, 2022)
Background: Craniosynostosis (CS) represents a highly heterogeneous genetic condition whose genetic background has not been yet revealed. The abnormality occurs either in isolated form or syndromic, as an element of hundreds of different inborn syndromes. Consequently, CS may often represent a challenging diagnostic issue. Methods: We investigated a three-tiered approach (karyotyping, Sanger sequencing, followed by custom gene panel/ chromosomal microarray analysis, and exome sequencing), coupled with prioritization of variants based on dysmorphological assessment and description in terms of human phenotype ontology. In addition, we have also performed a statistical analysis of the obtained clinical data using the nonparametric test χ2. Results: We achieved a 43% diagnostic success rate and have demonstrated the complexity of mutations’ type harbored by the patients, which were either chromosomal aberrations, copy number variations, or point mutations. The majority of pathogenic variants were found in the well-known CS genes, however, variants found in genes associated with chromatinopathies or RASopathies are of particular interest. Conclusion: We have critically summarised and then optimised a cost-effective diagnostic algorithm, which may be helpful in a daily diagnostic routine and future clinical research of various CS types. Moreover, we have pinpointed the possible underestimated co-occurrence of CS and intellectual disability, suggesting it may be overlooked when intellectual disability constitutes a primary clinical complaint. On the other hand, in any case of already detected syndromic CS and intellectual disability, the possible occurrence of clinical features suggestive for chromatinopathies or RASopathies should also be considered.